An important role for the activation peptide domain in controlling factor IX levels in the blood of haemophilia B mice - Begbie, Megan E; Mamdani, Asif; Gataiance, Sharon; Eltringham-Smith, Louise J; Bhakta, Varsha; Hortelano, Gonzalo; Sheffield, William P (Thrombosis and haemostasis, 2005)
The factors responsible for the removal of injected factor IX (fIX) from the blood of individuals with haemophilia B are only partly understood, and may include binding to endothelial or subendothelial sites, passive extravasation related to size or charge, or interactions requiring fIX activation. To investigate these issues, we have produced and characterised recombinant fIX proteins with amino acid changes: delta155-177, an internal deletion which removes most of the activation peptide while retaining the activation cleavage sites; S365A, which inactivates the serine protease activity of fIXa; and K5A, previously shown to eliminate fIX binding of endothelial/subendothelial collagen IV. All proteins were expressed in stably transfected HEK 293 cells, purified by immunoaffinity chromatography, and compared to the wild type HEK 293-derived protein (fIX (WT)). Mutant fIX proteins K5A and delta155-177 exhibited 72 and 202% of the specific activity of fIX (WT), respectively; S365A was without activity. Following intravenous injection in haemophilia B (fIX knockout) mice, recoveries did not differ for fIX (WT) and delta155-177, but were higher for K5A and S365A. The terminal catabolic half-life of delta155-177, alone among the mutants, was increased, by 45% versus fIX (WT). Nine hours post-injection, the observed areas under the clearance curve (AUCs) of delta155-177 and K5, but not S365A, were elevated 2-fold. delta155-177 was equally effective as fIX (WT) in reducing blood loss following tail vein transection in haemophilia B mice. Our results suggest that deletion of the multiple sites of fIX post-translational modification found within the activation peptide eliminated important fIX clearance motifs.